The End-use Electric Energy Consumption in Urban Areas: A GIS-based methodology. An application in the city of Naples. - Carpentieri, Gerardo; Favo, Federica (TeMA - Journal of Land Use, Mobility and Environment, 2017)
This work is part of the scientific research sector concerning the Government of Urban and Territorial Transformations in order to promote efficiency and reduction of energy consumption in urban areas. The contribution proposes a further deepening of the research work already carried out under the project Pon "Smart Energy Master" by the research group of the Laboratory of Territory, Mobility and Environmental (TeMA Lab) of Department of Civil, Architectural and Environmental Engineering, University of Naples Federico II. The aim is to assist public authorities, that also deal with the Urban Energy Governance, in determining the quantitative distribution of domestic and non-domestic electric energy consumption. Toward this goal, we use the Big Data, the Open Data and the Geographic Information System (GIS) techniques. In particular, this work developed a innovative GIS-based methodology that allows the knowledge, classification and representation of real electric energy consumption at micro scale for the domestic and non-domestic. Also, we validate the GIS-based methodology by an application at the city of Naples. We used the electric energy consumption data of year 2011 were given by Municipality Authority and Italian Revenue Agency. This will allow the identification of the electric energy problems present in the area of analysis in order to plan any intervention strategies. This contribution is divided into three main parts. In the first part, an analysis of the scientific literature is proposed on the theme of the Government of urban and territorial transformations and opportunities arising by Big Data, Open Data and GIS in the reduction of electric energy consumption. The second part explains the theoretical and technical phases that led to the development of the GIS-based methodology. In the last part, the application of the GIS-based methodology at the City of Naples is described.